DETERMINAN MOTIVASI DALAM BERWIRAUSAHA PADA MAHASISWA UNIVERSITAS SAMAWA SUMBAWA BESAR - Selviani, Rita; Sudiyarti, Nining; Rachman, Rosyidah (Fakultas Ekonomi dan Manajemen, 2023)
This research aims to determine the factors that influence entrepreneurial motivation at students of Samawa University, Sumbawa Besar, consisting of risk tolerance, self-efficacy and work freedom. This research uses an associative design which aims to determine the relationship or influence between two or more variables. The data used in this research is quantitative in the form of scoring results of respondents' responses in answering questions given through a questionnaire. This data was obtained directly from respondents, namely 54 students of Samawa University, Sumbawa Besar. The data that has been collected will be processed using the Statistical Package for the Social Sciences (SPSS) program and will then be studied using techniques including multiple linear regression analysis, partial parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and test the determinant coefficient (R2). The results of this study showed that partial risk tolerance did not have significant effect on entrepreneurial motivation, meanwhile self-efficacy and work had a positive and significant effect on entrepreneurial motivation at students of Samawa University, Sumbawa Besar. Furthermore, risk tolerance, self-efficacy and work freedom in simultaneously had a significant effect on entrepreneurial motivation at students of Samawa University, Sumbawa Besar. The ability of the variables risk tolerance, self-efficacy and work freedom on entrepreneurial motivation at students of Samawa University, Sumbawa Besar was 38%, while the remaining 62% was affected by other variables outside of this study, such as environmental factors, sociological factors, capital availability factors, personal factors and adversity quotient.